2019
DOI: 10.1590/2447-536x.v25i4.2019
|View full text |Cite
|
Sign up to set email alerts
|

Soft rot on the stems of Zamioculcas zamiifolia caused by Sclerotium rolfsii

Abstract: Zamioculcas zamiifolia (Araceae) is one of the most widely grown exotic species in Brazil as ornamental plants and in landscape design. Despite tolerating transport and being well adapted to low-light environments, this ornamental is attacked by different pathogens. Thus, the aim was to detect and identify the pathogen that causes stem rot in commercial Z. zamiifolia crops. Z. zamiifolia plants exhibiting stem rot symptoms were sent for phytosanitary diagnosis. In a culture medium, the fungal isolate obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…This fungus is common on several plant hosts including ornamental plants. Stutz et al (2019) utilized specific primers to diagnose the disease on ZZ plant (Zamioculcas zamiifolia) as it caused soft rot on the stems of the plant. The results showed that infections by Cercospora, compared to other fungi, was less frequent on ornamental plants tested.…”
Section: Discussionmentioning
confidence: 99%
“…This fungus is common on several plant hosts including ornamental plants. Stutz et al (2019) utilized specific primers to diagnose the disease on ZZ plant (Zamioculcas zamiifolia) as it caused soft rot on the stems of the plant. The results showed that infections by Cercospora, compared to other fungi, was less frequent on ornamental plants tested.…”
Section: Discussionmentioning
confidence: 99%
“…in purifying indoor air by eliminating pollutants such as benzene, ethylbenzene, toluene, and xylene (Toabaita et al, 2016). Despite its popularity, various diseases of Z. zamiifolia have been reported worldwide, including soft rot and foliar blight (Sanahuja et al, 2016;Seo et al, 2019;Stutz et al, 2020). Studies from Korea documented symptoms in Z. zamiifolia infected with Athelia rolfsii, including water-soaked stems, lower leaf chlorosis followed by stem collapse, and crown rot (Seo et al, 2019).…”
mentioning
confidence: 99%